Papillary Renal Cell Carcinoma Seeding along a Percutaneous Biopsy Tract - Deanne Soares; Nariman Ahmadi; Oana Crainic; John Boulas (Case Reports in Urology)
We report a case of tumour seeding caused by percutaneous biopsy of a papillary renal cell carcinoma detected on pathological assessment of the partial nephrectomy specimen in a 50-year-old male. Whilst percutaneous biopsy of renal masses is considered to be safe and can be a valuable tool in the assessment of certain renal lesions, it is not without risks. This rare complication should be taken into consideration before contemplating its use in a patient.